Thermoluminescence and radiocarbon dating of pre-colonial ceramics and organic midden material from the US Virgin Islands: outline for a revised chronology - Torres, Joshua; Toftgaard, Casper Jacobsen; Delbey, Thomas; Brewer, David; Farchette III, John; de la Fuente, Guillermo; Rasmussen, Kaare Lund (Springer, 2023)
A sample of 128 pottery shards curated by the National Museum of Denmark, from seven archaeological sites in the US Virgin Islands, has been dated using the thermoluminescence dating (TL) technique with the purpose of refining local pre-colonial pottery chronology. The results of the TL-dating generally confirm chronologies offered by Wild for St. John and there is considerable variation identified in traditional frameworks due to overlap in distributions of various pottery styles. The results of this study show that the Virgin Islands offer a viable space for the application of TL-dating, and that TL-dating offer a reliable addition to the traditional radiometric radiocarbon technique in pre-colonial midden contexts. Using the TL-technique for dating of pottery assemblages allows for a nuanced chronology and better understanding of settlement timing, socio-cultural interaction, and information transmission.
Keywords: US Virgin Islands; Pre-contact ceramics; Thermoluminescence dating; Radiocarbon dating; Migration